Recent advancements in software reliability assurance - Anand, Adarsh; Ram, Mangey (Boca Raton, FL : CRC Press, 2019)
The aim of this book is to provide a platform to academicians, practitioners, and researchers to understand current and future trends in software reliability growth modeling. Emphasis will be on qualitative work relevant to the theme with particular importance given to mathematical modeling for software reliability and various methods and applications of multi attributed decision making in governing the software performance. Presents software quality and security models Offers reliability analysis, assurance techniques for software systems Covers methodologies, tools, and practical applications of software reliability modeling and testing resources Includes robust reliability design techniques, diagnostic, and decision support Discusses stochastic modelling for software systems
OCLC-licensed vendor bibliographic record.
Keywords: Computer software -- Reliability; Software maintenance; COMPUTERS / Software Development & Engineering / Quality Assurance & Testing; MATHEMATICS / General; TECHNOLOGY / Electricity; TECHNOLOGY / Engineering / General